Apakah Belanja Pendidikan dan Kualitas Guru dapat Meningkatkan Kualitas Pendidikan? - Wulansari, Narulita Ratih; Khoirunurrofik, Khoirunurrofik (UI Scholars Hub, 2021)
This study aims to analyze the relationship between education expenditure and teacher quality on education quality at the senior secondary level in Indonesia. Based on data analysis across provinces using the Fixed Effect Method, an inverted U-shaped relationship was identified between education expenditure and education quality. This study also shows that teacher quality has a significant effect in improving education quality. The interregional analysis shows that education expenditure has an inverted U-shaped relationship and teacher quality has a positive relationship with education quality at the outside Java-Bali region. However, education expenditure and teacher quality do not show a significant result for the Java-Bali region. Overall, this study suggests that efficiency in education expenditure and teacher quality play an important role in improving education quality at the senior secondary level in Indonesia.